Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsbiomaterials.9b00514
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm Silk Matrices Coated with Functionalized Spider Silk Accelerate Healing of Diabetic Wounds

Abstract: Complex cutaneous wounds like diabetic foot ulcers represent a critical clinical challenge and demand a large-scale and low-cost strategy for effective treatment. Herein, we use a rabbit animal model to investigate efficacy of bioactive wound dressings made up of silk biomaterials. Nanofibrous mats of Antheraea assama silkworm silk fibroin (AaSF) are coated with various recombinant spider silk fusion proteins through silk–silk interactions to fabricate multifunctional wound dressings. Two different types of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
(112 reference statements)
1
20
0
Order By: Relevance
“… [ 85 ] Spider silk fusion proteins Nanofibrous mats of AaSF Efficient matrix remodelling of wounds. [ 93 ] Heparin or bemiparin CS hydrogels Improved diabetes-associated impaired wound healing. [ 87 ] Nucleic acids tFNAs Antioxidant activity via the Akt/Nrf2/HO-1 signaling pathway.…”
Section: Substances Applied In Diabetic Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 85 ] Spider silk fusion proteins Nanofibrous mats of AaSF Efficient matrix remodelling of wounds. [ 93 ] Heparin or bemiparin CS hydrogels Improved diabetes-associated impaired wound healing. [ 87 ] Nucleic acids tFNAs Antioxidant activity via the Akt/Nrf2/HO-1 signaling pathway.…”
Section: Substances Applied In Diabetic Wound Healingmentioning
confidence: 99%
“… 92 Nanofibrous mats of Antheraea assama silkworm silk fibroin are coated with various recombinant spider silk fusion proteins through silk–silk interactions to fabricate multifunctional wound dressings. 93 …”
Section: Substances Applied In Diabetic Wound Healingmentioning
confidence: 99%
“…In recent studies presented by Chouhan et al [81] and Liu et al [82], recombinant spider silk proteins were genetically modified with a motif from fibronectin to promote cell adhesion. Silk fibroin from silkworms was processed into nanofibrous mats and microporous scaffolds, and those were coated with the recombinant spider silk fusion protein (FN-4RepCT (FN-4RC)) ( Figure 8).…”
Section: Skin Regeneration and Wound Dressingsmentioning
confidence: 99%
“…104 Li et al prepared nanofiber dressing of SF encapsulating microparticles loaded with insulin. 105 Insulin stimulates keratinocyte and endothelial cell proliferation and migration, promoting wound reepithelialization and vascularization. These authors observed that the dressing improved the wound healing in diabetic rats due to a sustained release of the insulin during the wound healing progress.…”
Section: Natural Polymersmentioning
confidence: 99%
“…When mats were coated with both spider silk proteins, they had a faster wound healing, improved granulation, angiogenesis, collagen deposition, and reepithelialization than the uncoated or one single coat in diabetic wounds. 105 SF scaffolds were also used as skin substitutes, by seeding human adipose-MSCs on them. 106 Interestingly, when the scaffolds were decellularized they were almost as effective as the seeded scaffolds in the treatment of diabetic wounds.…”
Section: Natural Polymersmentioning
confidence: 99%